2011
DOI: 10.1038/nrrheum.2011.117
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacogenetics: implications for therapy in rheumatic diseases

Abstract: DMARDs not only improve the joint pain and swelling associated with rheumatoid arthritis (RA), but also slow down the joint damage associated with the disease. The efficacy of biologic therapies, introduced in the past decade for the treatment of RA, has been unequivocally established. Similarly, in addition to traditional drugs such as hydroxychloroquine, new biologic agents such as rituximab have been introduced for systemic lupus erythematosus in recent years. However, considerable variability occurs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 95 publications
0
60
0
2
Order By: Relevance
“…As a consequence, it has been difficult to relate the pharmacokinetics (PKs) of these drugs to their efficacy in different rheumatic conditions, as well as in relation to their mode of actions and adverse or side effects. There have been a number of reviews published on the PKs of HCQ and CQ in relation to application in rheumatic diseases to which the reader is referred (Rynes 1992;Tett et al 1993;McChesney and Fitch 1984;McChesney 1983;White 1985;Cutler et al 1988;Titus 1989;Cutler 1993;Tett 1993;Furst 1996;Davila and Ranganathan 2011).…”
Section: Pharmacokineticsmentioning
confidence: 98%
See 1 more Smart Citation
“…As a consequence, it has been difficult to relate the pharmacokinetics (PKs) of these drugs to their efficacy in different rheumatic conditions, as well as in relation to their mode of actions and adverse or side effects. There have been a number of reviews published on the PKs of HCQ and CQ in relation to application in rheumatic diseases to which the reader is referred (Rynes 1992;Tett et al 1993;McChesney and Fitch 1984;McChesney 1983;White 1985;Cutler et al 1988;Titus 1989;Cutler 1993;Tett 1993;Furst 1996;Davila and Ranganathan 2011).…”
Section: Pharmacokineticsmentioning
confidence: 98%
“…3a) or bioavailability (Fig. 3b) in patients with RA or SLE who have received HCQ Munster et al 2002;Carmichael et al 2013); (f) the possibility that pharmacogenomic influences affecting drug metabolism and drug transporters may influence responses to the anti-malarials in rheumatic patients (Davila and Ranganathan 2011); and, (g) differences in the ratios of the R(-)/S(?) enantiomers in blood or plasma C max , as well as plasma or urinary values of T 1/2 (Table 1; Figs.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…However, clinical studies indicate that, when given alone or in combination with methotrexate, hydroxychloroquine does not prevent joint destruction in 60%-70% of affected patients (58), suggesting that it may have limited use as an antiresorptive in most RA patients. CQ and hydroxychloroquine prevent acidification of the lysosomal compartment, but their mechanism of action is unclear, and reports of the effects of these drugs on OCs in vitro have been contradictory.…”
Section: Relb Is Required For Rankl-induced Traf3 Lysosomal Degradatimentioning
confidence: 99%
“…Although many of these inhibitors suppress osteoclastogenesis and bone resorption, none of them has progressed to clinical trials for the treatment of common bone diseases, such as postmenopausal osteoporosis or RA (4). Biologic inhibitors directed at pathogenetic cytokines, such as TNF, IL-1, and IL-6, have been approved for the treatment of inflammatory arthritis (57,58). However, these treatments fail to achieve remission in up to 40% of patients (57).…”
Section: Relb Is Required For Rankl-induced Traf3 Lysosomal Degradatimentioning
confidence: 99%
“…Several studies have shown the SNP G308A in the gene encoding TNF-a was associated with clinical responses to infliximab, etanercept and adalimumab, and most studies reported an increased efficacy. 37 Significant association was found between the FCGR2A H131R polymorphism and the response to treatment with infliximab, but not with the other two TNF inhibitors, etanercept and adalimumab. 38 In addition, IL-6R polymorphisms rs12083537, rs2228145 and rs4329505 have been shown to be potential predictors for response to tocilizumab in RA.…”
Section: Clinical Application Of Genetic Studies In Ramentioning
confidence: 91%